2020
DOI: 10.1155/2020/5073814
|View full text |Cite
|
Sign up to set email alerts
|

Could the Novel Oral Anticoagulants Be Used for Coronary Artery Aneurysm?

Abstract: Coronary artery aneurysms (CAAs) are uncommon in coronary angiography, and left main coronary artery aneurysms are rare. There is no consensus for the treatment of CAAs. A young patient with left coronary artery aneurysm diagnosed by coronary angiography and with recurrent acute myocardial infarction was treated with rivaroxaban and aspirin. The patient had no angina for 6 months. Novel oral anticoagulants combined with antiplatelet agents may be appropriate for the treatment of CAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…Clinical management of chronic anticoagulation treatment should carefully assess the ischemic risk and haemorrhagic danger of each patient individually. Contemporary literature supports the notion of DOAC's safe profile in the prevention of systemic embolism, even in cases with concomitant LV thrombus [34] in the present case the decision for chronic treatment with a DOAC was amenable to existent literature data displaying antithrombotic management in patients with systematic/arterial thromboembolic events [30][31][32][33]. Regarding cancer patients, the use of DOAC's has been described mainly in the context of deep vein thrombosis and pulmonary embolism [35].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Clinical management of chronic anticoagulation treatment should carefully assess the ischemic risk and haemorrhagic danger of each patient individually. Contemporary literature supports the notion of DOAC's safe profile in the prevention of systemic embolism, even in cases with concomitant LV thrombus [34] in the present case the decision for chronic treatment with a DOAC was amenable to existent literature data displaying antithrombotic management in patients with systematic/arterial thromboembolic events [30][31][32][33]. Regarding cancer patients, the use of DOAC's has been described mainly in the context of deep vein thrombosis and pulmonary embolism [35].…”
Section: Discussionsupporting
confidence: 68%
“…Antithrombotic treatment of patients with blood malignancies and arterial thrombosis can be challenging in daily clinical practice, while few reports in literature describe similar cases [30][31][32][33]. Clinical management of chronic anticoagulation treatment should carefully assess the ischemic risk and haemorrhagic danger of each patient individually.…”
Section: Discussionmentioning
confidence: 99%
“…However, case reports and small reviews have suggested that anticoagulation (with a direct oral anticoagulant or warfarin) may be acceptable in certain clinical scenarios, for example, when aneurysmal disease has resulted in thrombosis or embolization. 7 However, in the absence of high-risk features, some experts recommend antiplatelet therapy for 1 year after intervention or indefinitely if observation is chosen as the preferred regimen for medium-to-large fistulas. 8 Therefore, with this patient, we recommended dual antiplatelet therapy for 1 year following his coil embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Tras el diagnóstico, se realizó seguimiento con terapia antiplaquetaria simple (TAPS) con aspirina, al cual se le propuso agregar un nuevo anticoagulante oral (NACO), como rivaroxaban, por negación del paciente a usar Warfarina. Se realizó un seguimiento por 6 meses, sin recurrencia del SCA ni dolor pectoral (Yan et al 2020).…”
Section: Pacientesunclassified